Pengembangan Aplikasi Perangkat Bergerak Berbasis Android Untuk Survei Kepuasan Masyarakat Dengan Metode Mobile-D (Studi Kasus : RSUD Ngudi Waluyo Wlingi Kabupaten Blitar) - Martantio Wicaksono; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ngudi Waluyo Wlingi Regional General Hospital (RSUD) is one of the public health services that is very much requested by the community regarding the quality of services available at the institution. So far the Ngudi Waluyo Wlingi Regional Hospital has taken data from the Community Satisfaction Survey by distributing questionnaires in an effort to obtain community assessments regarding the quality of existing services. However, the use of questionnaire questionnaires was felt to be less effective and efficient in terms of data preparation and processing. RSUD to initiate an Android-Based Mobile Device Application for the Community Satisfaction Survey. This application was designed using the Mobile-D method and implemented with the Java programming language, using a local server with MySQL database and using the IDE android studio. In the system test this application uses validation, compatibility, and usability testing methods. Based on the design results in this study sixteen functional requirements and three non-functional requirements were obtained. Based on the results of the validation test it can be concluded that the functional and non-functional requirements of the community satisfaction survey application are valid, based on the results of usability testing, the SUS (System Usability Scale) score is 70.9375 which means the application is easy to use, and on the test results full compatibility status that means the application can be run on several mobile devices with different API types and levels.